Platelet-Rich Plasma in Reconstruction of Posterior Meatal Wall after Canal Wall Down Mastoidectomy - Elbary, Mohammad El-Sayed Abd; Nasr, Wail Fayez; Sorour, Samir Sorour (International Archives of Otorhinolaryngology, 2018)
Introduction Canal wall down (CWD) mastoidectomy has many drawbacks, including chronic otorrhea not responding to medications, granulations, dizziness on exposure to cold or hot water, and tendency of debris accumulation in the mastoid cavity, demanding periodic cleaning. Many of these problems can be solved by reconstruction of the posterior meatal wall (PMW).Objectives To assess the results of PMW reconstruction after CWD mastoidectomy for cholesteatoma using titanium mesh and platelet-rich plasma (PRP) mixed with bone pate.Methods This study was conducted with 20 patients that have atticoantral chronic suppurative otitis media. All cases were subjected to CWD mastoid surgery with complete elimination of the disease and reconstruction of the PMW by titanium mesh and the mixture of PRP with bone pate. All patients were exposed to a full preoperative evaluation and full postoperative assessment of the complications, the appearance of the external auditory canal contour, and the hearing gain expressed by the change of the air bone gap postoperatively.Results The PMW reconstructed by titanium mesh and the mixture of PRP with bone pate showed a smooth contour. During the follow-up of 12 to 36 months, the postoperative appearance of the external auditory canal contour was found to be smooth without hidden pouches, irregularities or stenosis in all cases. No granulation, foreign body reaction, or extrusion and/or displacement of the titanium mesh were registered. No facial palsy or recurrent cholesteatoma was reported.Conclusion The surgical reconstruction of the PMW using PRP, bone pate and titanium mesh after CWD mastoidectomy appears to be reliable without considerable complications, giving a smooth appearance to the PMW.
Keywords: platelet-rich plasma; titanium; cholesteatoma